AICAr to SAICAr ratio can serve as additional marker of AICAr use. Issue 11 (16th November 2022) - Sobolevsky, Tim; Piper, Thomas; Ahrens, Brian; Thevis, Mario
Abstract: AICAr (5‐aminoimidazole‐4‐carboxamide‐1‐β‐D‐ribofuranoside, commonly referred to as AICAR) is an adenosine monophosphate‐activated protein kinase agonist previously investigated for its therapeutic potential which has been shown to improve exercise performance in laboratory animals. For this reason, the World Anti‐Doping Agency prohibits the use of AICAr in sports. AICAr can easily be detected by means of liquid chromatography–mass spectrometry, but being an endogenous metabolite, it cannot be discriminated from AICAr of a non‐natural origin. Population‐based concentration thresholds have been suggested as a means to identify suspicious samples that would require further analysis by carbon isotope ratio mass spectrometry (CIR); however, it remains at the discretion of the laboratory how to apply them. Here, the urinary ratio of AICAr to SAICA‐riboside (SAICAr) that is a closely related purine metabolite was investigated. In an athlete population of 5517 samples, this ratio was relatively narrowly distributed with median values and 99th percentiles of 3.3 and 9.3, and 4.2 and 14 in male and female athletes, respectively. Analysis of urine samples obtained from an AICAr administration study demonstrated that the AICAr/SAICAr ratio can serve in addition to AICAr concentration as a valuable diagnostic trigger for follow‐up analysis by CIR. Conceivably, this combination can offer better retrospectivity than AICAr concentration alone by allowing to decrease the AICAr concentration threshold without significantly increasing the number of suspicious samples. Abstract : The urinary ratio of AICAr to SAICA‐riboside (SAICAr) that is a closely related purine metabolite has been investigated. In the studied athlete population, this ratio was narrowly distributed with median value and 99th percentile of 3.3 and 9.3, and 4.2 and 14 in male and female athletes, respectively. Analysis of urine samples obtained from AICAr administration study demonstrated that the AICAr/SAICAr ratio can serve as a valuable diagnostic marker to trigger a follow‐up analysis by carbon isotope ratio mass spectrometry.